(untitled) (Global Journal of Science Frontier Research, 2024)
In recent years the impact of toxic phytoplankton on ecological balance has attracted more and more ecologists to study In this paper we develop and analyze a model with three interacting species poisonous and nontoxic phytoplankton and zooplankton including zooplankton avoiding toxic phytoplankton in the presence of nontoxic phytoplankton and the impact of human harvest on the coexistence of these three species We first introduce the poisonous avoidance coefficient and the human harvest of nontoxicphytoplankton and zooplankton to investigate its impact on species coexistence We not only find that has a particular effect on the coexistence of these three species But also that human harvest is an essential factor determining the coexistence of these three species Secondly pregnancy delay and toxin onset delay are introduced to explore the influence of time delay on the behavior of dynamic systems When the delay value exceeds its critical value the system will lose stability and go through Hopf bifurcation After that we use the principle of Pontryagin s maximum to study the optimal tax policy without delay We obtained the optimal path of the optimal tax policy Finally we carry out numerical simulations to verify the theoretical results